Youth and charismatic Christianity in the Dwars River Valley, Stellenbosch - Du Plessis, Miemie (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Sociology and Social Anthropology))--University of Stellenbosch, 2009.